Diagnostic accuracy of the appearance of Nigrosome-1 on magnetic resonance imaging in Parkinson's disease: A systematic review and meta-analysis. (September 2020) - Chau, Minh Toan; Todd, Gabrielle; Wilcox, Robert; Agzarian, Marc; Bezak, Eva
Abstract: Introduction: There is currently no definitive diagnostic test for Parkinson's disease (PD) and the current diagnostic procedure primarily relies on clinical manifestations. A hypointense appearance of nigrosome-1 (or absence of the "swallow tail" sign) on magnetic resonance imaging (MRI) has been proposed as a biomarker for PD. This meta-analysis examined the diagnostic accuracy of the appearance of nigrosome-1 on Magnetic Resonance Imaging (MRI) in differentiating idiopathic PD patients from healthy adults. Methods: Databases (MEDLINE, Embase, Scopus) were searched from 2012 (first publication of nigrosome-1 MRI scans) up until September 2019. Two researchers independently screened all titles and abstracts to identify studies that met the inclusion criteria and extracted relevant articles in a uniform manner. Two authors independently extracted data and assessed the risk of bias using a customized QUADAS-2 tool. Pooled sensitivity and specificity were calculated using a hierarchical summary receiver operating characteristic approach, as were positive and negative likelihood ratios. Results: Nineteen studies containing a total of 1508 participants (903 idiopathic PD patients and 605 healthy controls) were included. The overall sensitivity and specificity were 0.94 (95%CI, 0.93–0.96) and 0.90 (95%CI, 0.88–0.92), respectively. The likelihood ratios for positive and negative test results were 9.72 (95%CI, 5.58–16.04) and 0.08 (95%CI, 0.05–0.12). The pooled area under the receiver operating characteristics curve (AUC) in the diagnosis of idiopathic PD was 0.98. Conclusions: Visual assessment of the nigrosome-1 appearance, at 3 or 7T, yields excellent diagnostic accuracy for differentiating idiopathic PD from healthy adults. Highlights: Rigorous meta-analysis synthesized data on pooled sensitivity and specificity. Diagnostic accuracy of the appearance of nigrosome-1 on MRI is excellent. The pooled area under the receiver operating characteristics curve (AUC) in the diagnosis of idiopathic PD was 0.98.